2019
DOI: 10.15430/jcp.2019.24.3.139
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Adverse Outcome Pathway Relevant to Carcinogenicity Induced by Sulfuric Acid in Strong Inorganic Acid Mists

Abstract: Based on epidemiological studies, an International Agency for Research on Cancer Working Group determined that strong inorganic acid mists containing sulfuric acid are carcinogenic to human even though, sulfuric acid, per se, is not. Accumulative studies indicate that there is a link between chronic occupational exposure to sulfuric acid mists and an increased risk of laryngeal cancer. Unintended, acute exposure to sulfuric acid mists can cause corrosive damage to target tissues depending on the route of expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Although some evidence showed that gastroesophageal reflux was an important risk factor of stomach cancer [23], it is unclear whether inhalation and subsequent ingestion of acid mists can cause similar effects. Since low pH can increase instability in chromosomes and DNA, it has been proposed that acid mists cause cancers through genotoxic effects [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although some evidence showed that gastroesophageal reflux was an important risk factor of stomach cancer [23], it is unclear whether inhalation and subsequent ingestion of acid mists can cause similar effects. Since low pH can increase instability in chromosomes and DNA, it has been proposed that acid mists cause cancers through genotoxic effects [24].…”
Section: Discussionmentioning
confidence: 99%
“…The byproduct, sulfuric acid (H 2 SO 3 ), is an extremely hazardous substance, which causes stinging, burning, and eye irritation. A deep breath of sulfuric acid vapor, even in small amounts, can cause coughing and a risk of laryngeal cancer depending on the human sensitive group, time, and concentration to which they were exposed [12,38,39]. Another byproduct, nitric Acid (HNO 3 ), is an extremely hazardous gas, which has effects on the lungs caused by inhalation of a wide range of gases.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…As a result, sulfuric acid was one of the most important factors that to haze and smog events (Li et al, 2011). It had been reported that PM 2.5 for every 1µg/m increase in concentration, the mortality rate of urban population would increase by 25 per million people (Yang et al, 2019), and that the concentration levels of PM 10 were strongly related to children's hospitalization for asthma and tracheitis (Perez-Diaz et al, 2017). Sulfuric acid was also one of the culprits for acid rain (Li et al, 2021a).…”
Section: Source Of Sulphuric Acid In Cfsmentioning
confidence: 99%